2001
DOI: 10.1038/ng577
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in IHH, encoding Indian hedgehog, cause brachydactyly type A-1

Abstract: Brachydactyly type A-1 (BDA-1; MIM 112500) is characterized by shortening or missing of the middle phalanges (Fig. 1a). It was first identified by Farabee in 1903 (ref. 2), is the first recorded example of a human anomaly with Mendelian autosomal-dominant inheritance and, as such, is cited in most genetic and biological textbooks. Here we show that mutations in IHH, which encodes Indian hedgehog, cause BDA-1. We have identified three heterozygous missense mutations in the region encoding the amino-terminal sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 20 publications
8
190
0
3
Order By: Relevance
“…In studying a mouse model for BDA1 (see Fig. 3), caused in humans by mutations in Indian hedgehog (IHH; Gao et al, 2001), Gao et al (2009) showed that this condition was caused by an impaired distal outgrowth of the digit condensation due to reduced commitment of distal progenitor cells. Ihh is produced by cells within the cartilage condensation and then diffuses across the growth plate, thereby forming a gradient .…”
Section: Developmental Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In studying a mouse model for BDA1 (see Fig. 3), caused in humans by mutations in Indian hedgehog (IHH; Gao et al, 2001), Gao et al (2009) showed that this condition was caused by an impaired distal outgrowth of the digit condensation due to reduced commitment of distal progenitor cells. Ihh is produced by cells within the cartilage condensation and then diffuses across the growth plate, thereby forming a gradient .…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…In Ror W749X/ W749X mice, the elongation defect is severe and no medial phalanx is formed. presumption, BDA1 patients often exhibit a short stature (Farabee, 1903;Gao et al, 2001). Hence, in addition to the condensation defect, a growth plate defect might contribute to further shortening of the digits in BDA1.…”
Section: Growth and Maintenance Of Digits And Jointsmentioning
confidence: 99%
“…Ihh knockout mice exhibit strongly reduced chondrocyte proliferation, maturation of chondrocytes at inappropriate position, and a failure of osteoblast development in endochondral bones (St-Jacques et al, 1999). In humans, homozygous mutations in IHH cause acrocapitofemoral dysplasia (Hellemans et al, 2003), an autosomal recessive disorder with short stature and coneshaped epiphyses in hands and hips, and heterozygous mutations in the signaling domain lead to brachydactyly type A1 (Gao et al, 2001). In addition, Col10 expression was absent in the humerus and radius/ulna of the mutant at E15.5, indicating the failure to form proper hypertrophic chondrocytes.…”
Section: Ror2 Is Required For Growth Of the Appendicular Skeletonmentioning
confidence: 99%
“…The absence of mineralized bone structures in Ihh-deficient animal indicates a role for Ihh in the coordination of multiple cellular events during endochondral bone development including chondrocyte proliferation and differentiation as well as osteoblast differentiation [St.-Jacques et al, 1999]. Mutations in the Ihh gene have been linked to two inherited skeletal developmental defects: brachydactyly type A-1 and acrocapitofemoral dysplasia, clearly implicating Ihh as a key regulator of skeletal development in humans [Gao et al, 2001;Hellemans et al, 2003]. In this review, we will discuss the multiple roles that Vortkamp et al [1996] first demonstrated that Ihh and parathyroid hormone related peptide (PTHrP) participate in a feedback loop, which coordinates chondrocyte proliferation and differentiation in fetal developing bones (Fig.…”
mentioning
confidence: 99%